2009
DOI: 10.1143/jjap.48.07gb02
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiative Investigation of Photodecomposition of Poly(di-n-hexylsilane) Thin Films Using Piezoelectric Photothermal Spectroscopy

Abstract: To investigate the photodecomposition mechanism of poly(di-n-hexylsilane) (PDHS), the ultraviolet (UV) light irradiation time dependence of the optical absorption (OA) and the piezoelectric photothermal (PPT) signals were measured in vacuum. A strong OA peak at 370 nm and a broad OA band at approximately 320 nm related to the all-trans and helical conformations, respectively, were observed. With increasing UV light irradiation time, their intensities decreased and blue shifts were observed because of the decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The piezoelectric photothermal (PPT) technique has been adopted to investigate the non-radiative recombination of photoexcited carriers in semiconductors. [24][25][26][27] Because this technique detects heat and elastic waves caused by the nonradiative recombination, 28) a PPT signal also includes the thermal properties. In fact, Horita et al reported that the thermal properties of Si, InP and Ta were determined by photoacoustic (=photothermal) signals detected by LiNbO 3 transducer.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric photothermal (PPT) technique has been adopted to investigate the non-radiative recombination of photoexcited carriers in semiconductors. [24][25][26][27] Because this technique detects heat and elastic waves caused by the nonradiative recombination, 28) a PPT signal also includes the thermal properties. In fact, Horita et al reported that the thermal properties of Si, InP and Ta were determined by photoacoustic (=photothermal) signals detected by LiNbO 3 transducer.…”
Section: Introductionmentioning
confidence: 99%